Peningkatan Kapasitas Petani Cabai melalui Farmers Field School - Friska Anggraini Barus; Intan Pulungan; Muhammad Yusuf Dibisono; Marzuti Isra; Nurkhotimah Sinaga; Atia Abel Pratiwi; Purjianto Purjianto; Mardiah Mardiah (Journal of Social Responsibility Projects by Higher Education Forum, 2026)
This community service program was conducted in Galudra Village, Cugenang District, Cianjur Regency, West Java Province, Indonesia, as part of the Bertani untuk Negeri (Farming for the Nation) Batch 9 Program organized by the Edufarmers International Foundation. The program targeted nine smallholder chili farmers who encountered several cultivation-related challenges, including limited knowledge of Good Agricultural Practices (GAP), heavy dependence on synthetic pesticides, minimal utilization of biofertilizers and botanical pesticides, and inadequate technical assistance in farm management. These constraints contributed to suboptimal productivity, increased production costs, and limited adoption of sustainable agricultural practices. This community service initiative aimed to enhance farmers' knowledge and technical capacity in implementing GAP through a participatory Farmers Field School (FFS) approach. The implementation methods consisted of baseline field observations, identification of farmers' needs, regular field monitoring, four FFS sessions, establishment of demonstration and mini-demonstration plots, practical training on the production of Plant Growth-Promoting Rhizobacteria (PGPR), amino acid liquid organic fertilizer, botanical pesticides, and pesticide wetting agents, followed by continuous mentoring and evaluation. The program contributed by introducing an integrated field-based extension model that combined theoretical learning with hands-on practice, thereby accelerating farmers' adoption of sustainable cultivation technologies. Furthermore, the initiative encouraged the utilization of locally available resources to produce environmentally friendly and cost-effective agricultural inputs. The results demonstrated that farmers improved their understanding and practical skills in applying GAP principles, acquired the ability to independently produce and apply PGPR, liquid organic fertilizer, and botanical pesticides, actively participated in all FFS activities, and gradually adopted more effective, efficient, and sustainable chili cultivation practices. These findings indicate that the participatory FFS model is an effective community empowerment strategy for strengthening farmers' capacities and can be replicated in other horticultural production areas.